2020
DOI: 10.1161/hypertensionaha.120.15019
|View full text |Cite
|
Sign up to set email alerts
|

Beat-to-Beat Blood Pressure Variability in the First Trimester Is Associated With the Development of Preeclampsia in a Prospective Cohort

Abstract: Women with preeclampsia, a hypertensive disorder of pregnancy, exhibit greater beat-to-beat blood pressure variability (BPV) in the third trimester after clinical onset of the disorder. However, it remains unknown whether elevated BPV precedes the development of preeclampsia. A prospective study cohort of 139 women (age 30.2±4.0 years) were enrolled in early pregnancy (<14 weeks gestation). BPV was quantified by time domain analyses of 10-minute continuous beat-to-beat blood pressure recordings via finger p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Moreover, AS is significantly higher in women with HDPs compared to normotensive pregnancies and further increases with disease severity [52] . In recent studies, we and others have demonstrated that AS measurements can detect altered hemodynamic responses in the first trimester of pregnancy in women who subsequently develop HDPs [53] , [54] , [55] , [56] , [57] , [58] . PWA parameters, CO, and FMD are also outcomes of interest in our study as they provide complementary information regarding overall vascular function and have been reported to be associated with HDPs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AS is significantly higher in women with HDPs compared to normotensive pregnancies and further increases with disease severity [52] . In recent studies, we and others have demonstrated that AS measurements can detect altered hemodynamic responses in the first trimester of pregnancy in women who subsequently develop HDPs [53] , [54] , [55] , [56] , [57] , [58] . PWA parameters, CO, and FMD are also outcomes of interest in our study as they provide complementary information regarding overall vascular function and have been reported to be associated with HDPs.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship was not previously described and should be used as a diagnostic tool for selecting a high cardiovascular risk population with enhanced stress blood pressure reactivity [Munakata, 2018] by relatively simple arterial blood pressure standard deviation evaluation method. The coexistence of the enhanced short‐term BPV and blood pressure surges in preeclampsia [Nuckols et al, 2020] and pheochromocytoma [Bisogni et al, 2019] supports the BPV for predicting abrupt blood pressure elevations in susceptible individuals [Dawson et al, 2000; Tang et al, 2020]. On the other hand, the pharmacological and nonpharmacological approaches aimed to decrease enhanced beat‐to‐beat BPV may be employed to prevent abrupt blood pressure elevation and its malicious cardiovascular consequences.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that the expected standard-of-practice is that reported PWV measurements are actually the average of two consecutive measurements or the median of three consecutive measurements if the difference between the first two exceeds 0.5 m/s [63]. [340,350,318,341,319,352,321,338,342,345,354,343,160,355,346,323,357,348,358,359,333,360,169,329,361,330,339,362,335,336,363,364] Peripheral arterial vasculature 16 [365, 349, 344, 351, 347, 337, 353, 322, 356, 324-327, 334, 328, 331] Carotid artery 2 [320,125] Aspect of vasculature assessed Arterial stiffness 49 [349, 340, 332, 350, 318, 344, 341, 351, 347, 319, 320, 352, 321, 337, 338, 353, 342, 322, 345, 354, 343, 160, 355, 346, 356, 125, 323, 324, 357, 348, 358, 325-327, 359, 333, 334, 360, 328, 169, 329, 361, 330, 339, 362, 335, 336, 363, 331, 364] Blood pressure 1 [349] Technique SphygmoCor device 12 [340,341,320,352,…”
Section: Analytic Considerationsmentioning
confidence: 99%